Loss of TBK1 is a frequent cause of frontotemporal dementia in a Belgian cohort. (15th December 2015) - Gijselinck, Ilse; Van Mossevelde, Sara; van der Zee, Julie; Sieben, Anne; Philtjens, Stéphanie; Heeman, Bavo; Engelborghs, Sebastiaan; Vandenbulcke, Mathieu; De Baets, Greet; Bäumer, Veerle; Cuijt, Ivy; Van den Broeck, Marleen; et al.
Abstract : Objective: To assess the genetic contribution of TBK1, a gene implicated in amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTD), and FTD-ALS, in Belgian FTD and ALS patient cohorts containing a significant part of genetically unresolved patients. Methods: We sequenced TBK1 in a hospital-based cohort of 482 unrelated patients with FTD and FTD-ALS and 147 patients with ALS and an extended Belgian FTD-ALS family DR158. We followed up mutation carriers by segregation studies, transcript and protein expression analysis, and immunohistochemistry. Results: We identified 11 patients carrying a loss-of-function (LOF) mutation resulting in an overall mutation frequency of 1.7% (11/629), 1.1% in patients with FTD (5/460), 3.4% in patients with ALS (5/147), and 4.5% in patients with FTD-ALS (1/22). We found 1 LOF mutation, p.Glu643del, in 6 unrelated patients segregating with disease in family DR158. Of 2 mutation carriers, brain and spinal cord was characterized by TDP-43-positive pathology. The LOF mutations including the p.Glu643del mutation led to loss of transcript or protein in blood and brain. Conclusions: TBK1 LOF mutations are the third most frequent cause of clinical FTD in the Belgian clinically based patient cohort, after C9orf72 and GRN, and the second most common cause of clinical ALS after C9orf72 . These findings reinforce that FTD and ALS belong to the same disease continuum.